Stable and low-threshold photon upconversion in nondegassed water by organic crystals - Murakami, Yoichi; Enomoto, Riku (Frontiers in Chemistry, 2023)
Photon upconversion (UC) is a technology that converts lower-energy photons (longer wavelength light) into higher-energy photons (shorter wavelength light), the opposite of fluorescence. Thus, UC is expected to open a vast domain of photonic applications that are not otherwise possible. Recently, UC by triplettriplet annihilation (TTA) between organic molecules has been studied because of its applicability to low-intensity light, although the majority of such studies have focused on liquid samples in the form of organic solvent solutions. To broaden the range of applications, solid-state UC materials have been an active area of research. We recently developed air-stable, high-performance molecular UC crystals that utilize a stable solid-solution phase of bicomponent organic crystals. This article begins with a brief overview of previous challenges in developing and improving solid-state TTA-UC materials. Then, we briefly review and explain the concept as well as advantages of our molecular solid-solution UC crystals. We applied these organic crystals for the first time to a water environment. We observed blue UC emission upon photoexcitation at 542 nm (green-yellow light) and then measured the excitation intensity dependence as well as the temporal stability of the UC emission in air-saturated water. These organic crystals were stable, functioned with a low excitation threshold intensity of a few milliwatts per square centimeter, and exhibited high photo-irradiation durability at least over 40 h in nondegassed water; indicating that the developed organic crystals are also viable for aqueous conditions. Therefore, the organic crystals presented in this report are expected to extend the domain of UC-based photonic applications in practical water systems including in vivo diagnostic, clinical, and therapeutic applications.